PRODUCTION OF IRON OF CINDER IN ROTARY FURNACES - D. M. Kukuj; L. E. Rovin; S. L. Rovin; V. A. Matochkin; S. V. Terletskij; V. N. Prohorenko (Литьë и металлургия)
The first positive results of iron production (recycling) of disperse oxide waste in experimental-industrial rocking furnace are presented.